Pengaruh Penerapan Good Governance dan Standar Akuntansi Pemerintahan terhadap Akuntabilitas Keuangan - Zeyn, Elvira (Jurnal Trikonomika, 2011)
Financial reporting play a mayor role in fulfilling governmentâs duty to be publicly accountable in a democratic society. Government accounting shall be performed according to generally accepted accounting practice. The purpose of this study are to analyze the influence of implementation good governance, accounting standards of government to financial accountability. The research method used were desciptive and verificativ. Analysis method used the multiple regression with the primary data. The data collected from survei toward the head of SKPD in Kabupaten Sukamara, Central Kalimantan. The results of study show that implementation good governance have not significant influence the financial accountability; implementation accounting standards of government significantly influence the financial accountability.